Proceedings of the Tenth Annual ACM/IEEE International Conference on Human-Robot Interaction Extended Abstracts 2015
DOI: 10.1145/2701973.2701982
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating Stereoscopic Video with Head Tracking for Immersive Teleoperation of Mobile Telepresence Robots

Abstract: Our research focuses on improving the effectiveness and usability of driving mobile telepresence robots by increasing the user's sense of immersion during the navigation task. To this end we developed a robot platform that allows immersive navigation using head-tracked stereoscopic video and a HMD. We present the result of an initial user study that compares System Usability Scale (SUS) ratings of a robot teleoperation task using head-tracked stereo vision with a baseline fixed video feed and the effect of a l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…This was generally indicated by statements that participants "had never interacted with our robots before" [190]. Finally, 35 studies explicitly mentioned participants who had specific expertise as roboticists alongside non-experts, e.g., [191,192], and often as the primary target group, e.g., [193][194][195][196]. Only six studies reported purposefully excluding those with robotics expertise [197][198][199][200][201].…”
Section: Domain Expertisementioning
confidence: 99%
“…This was generally indicated by statements that participants "had never interacted with our robots before" [190]. Finally, 35 studies explicitly mentioned participants who had specific expertise as roboticists alongside non-experts, e.g., [191,192], and often as the primary target group, e.g., [193][194][195][196]. Only six studies reported purposefully excluding those with robotics expertise [197][198][199][200][201].…”
Section: Domain Expertisementioning
confidence: 99%
“…In immersive virtual reality environments, remote users typically use HMDs to observe the local environment. Kratz et al [7,42] evaluated the use of a head-mounted device with tracking for remote collaboration in robotic telepresence and concluded that the use of an HMD to control the local view reduced task error rates and improved perceived collaboration success and view quality. Martins et al [8,43] used a head-mounted display on a control alternative search-and-rescue (SAR) robot, whereby the operator was able to perceive a three-dimensional-corrected image of the robot world transmitted by a pair of stereo cameras on the robot.…”
Section: Movable Telepresence Robots (Mtrs)mentioning
confidence: 99%
“…In traditional mixed-reality remote collaboration, the video capture device is typically placed in a fixed position in the local environment [4] or on a local user's HMD [5], providing a fixed perspective or the local user's first-person view of the local environment, and remote users cannot actively and freely switch views. In recent research on remote presentations, researchers have mainly deployed video capture devices on wheeled robots [6][7][8] or drones [9,10], allowing remote users to move the viewing perspective by operating these devices. However, these systems have limitations in terms of control freedom and accuracy, which prevent remote users from freely and accurately observing the local environment.…”
Section: Introductionmentioning
confidence: 99%
“…However, regular remote presence robots and consumer telepresence robots project their camera vision through a video feed on a twodimensional screen. As depth perception is essential in most operations, the lack of a stereoscopic display will hamper a robot operator's judgement about distance, when in turn might lead to unwanted collisions due to misestimations of the surrounding [5][6] [11].…”
Section: Introductionmentioning
confidence: 99%